Both Basal and Acute Restraint Stress-Induced c-Fos Expression Is Influenced by Age in the Extended Amygdala and Brainstem Stress Centers in Male Rats - Kovács, László Ákos; Schiessl, Josef Andreas; Nafz, Anna Elisabeth; Csernus, Valér; Gaszner, Balázs (Frontiers in Aging Neuroscience, 2018)
The hypothalamus-pituitary-adrenal axis (HPA) is the main regulator of the stress response. The key of the HPA is the paraventricular nucleus of the hypothalamus (PVN) controlled by higher-order limbic stress centers. The reactivity of the HPA axis is considered to be a function of age, but to date, little is known about the background of this age-dependency. Sporadic literature data suggest that the stress sensitivity as assessed by semi-quantitation of the neuronal activity marker c-Fos may also be influenced by age. Here we aimed at investigating the HPA activity and c-Fos immunoreactivity two hours upon acute restraint stress in eight different age groups in the rat. We hypothesized that the function of HPA axis (i.e. PVN c-Fos and blood corticosterone level), the neuronal activity of eight stress-related limbic areas [i.e. medial (MeA), central (CeA), basolateral (BLA) nuclei of the amygdala, the oval (ovBNST), dorsolateral (dlBNST), dorsomedial (dmBNST), ventral (vBNST) and fusiform (fuBNST) divisions of the bed nucleus of the stria terminalis], and two brainstem stress centers such as the centrally projecting Edinger-Westphal nucleus (cpEW) and dorsal raphe nucleus (DR) show age dependency in their c-Fos response. Our results indicate that the stress-induced rise in blood corticosterone titer was lower in young age reflecting relatively low HPA activity. All eleven examined brain areas showed significant c-Fos response which appeared to be a function of age. The c-Fos response peaked at two months of age and gradually decreased with age except for BLA and BNSTv. The reduction was significant from 3 months of age on in two areas (CeA and DR) from 6 months on in 6 areas (MeA, ovBNST, dmBNST, fuBNST, PVN, cpEW) and from 12 months of age in the dlBNST. Unexpectedly, the CeA, ovBNST and cpEW showed a considerable basal c-Fos expression in one-month-old rats. We conclude that the examined limbic centers show an age- and brain area dependent dynamics in the stress-induced neuronal activity pattern, which may contribute to the age dependence of the stress reactivity. Further studies are in progress to identify the neurochemical identity of neurons showing age-dependent basal and/or stress-induced c-Fos expression.